Metrópolis and telematic networks (2003)
The urbanization process needs two readings, a general, like the transformation of the rural societies to urban societies on world-wide scale and another specific one, as the growth of the cities and increase of the complexity degrees until conforming poles of regional attraction that absorb and regulate the relations and messages of their rural surroundings, it means, they are transformed into Territorial attractors, process that is defined as metropolization. Nevertheless, nowadays it is not possible to understand the Latin American metropolis without the reference to the process of economic globalization of the country, still more when the Latin American society is vulnerable and permeable to the exogenous messages and decisions. The economic relations and of consumption are every time more telematics and therefore exiled; the cities limits, are stumped, whereas the approaches that reinforce the relational points of view, are fortified, conceptualizing the city like attractors centers of the urban relations; where the rural areas are absorbed by the urban weave within the framework of a process of reurbanization of the forms to live in the metropolitan space. It means, it is possible to be attending a new character of the centrality of the city: In addition to the singularity in a geographic space, it has a singularity in a relational space of «directed consumption». It is possible to be attending a new character of the rural peripheries: of the rural dependency with passive function; to an interdependence with the urban centers with active function in economic, social and of the power terms; where problematic of the cities sense and peripheral territories, they imply the revision of the theoretical marks from which we verified these signals of mutation.